INVENTARISASI STOK BIOMASSA DAN KARBON AKAR, SERESAH, NEKROMASSA DAN TANAH HUTAN TANAMAN JATI KPH KEBONHARJO, PERUM PERHUTANI UNIT I JAWA TENGAH - , DIANA PUSPITASARI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
Forest carbon stock measurement can describe the amount of CO2 gases in the atmosphere is absorbed by plants and is required to support the implementation of the REDD+ program. In Perhutani, teak plantations area covered 62,27 % of the total production forest area. Carbon stock measurement of the root, litter, necromass and soil in teak plantations were still rare. This research aimed to obtain allometric equation of root biomass and carbon, to estimate potency of biomass and carbon in the root, litter, necromass and soil, to calculate the average percentage of the carbon content of biomass from root, litter, necromass and the average percentage of soil organic carbon content. The study was carried out at KPH Kebonharjo, Perhutani Unit I, Central Java. The number of sample to form the allometric equation were 36 trees, from stands age class I - VI. The measurement of teak root sample was carried out destructively. Diameter at breast height was used as predictor variabel for teak root biomass and carbon. The sample of litter, necromass and soil was obtained by making plot at 12 compartments of age class I â VI, 3 plots per compartment, purposively. The measurement of carbon content was carried out by Walkley and Black method with spectrophotometry. The allometric equation between diameter at breast height with the root biomass was Ba = 0,028(DBH) 2,364 (kg, cm, R 2 = 0,974). The allometric equation between diameter at breast height with the root carbon was Ka = 0,012(DBH) 2,377 (kg, cm, R 2 = 0,971). The potency of teak root biomass and carbon from production forest at KPH Kebonharjo were 10,4 tons/ha and 4,6 tons/ha, respectively. The potency of litter biomass and carbon were 5,9 tons/ha and 1,9 tons/ha, respectively. The potency of necromass biomass and carbon were 0,035 tons/ha and 0,014 tons/ha, respectively. The potency of soil organic carbon at 0-10 cm depth was 15,91 tons/ha, at 10-20 cm depth was 10,4 tons/ha and at 20-30 cm depth was 8,71 tons/ha. The average % C (carbon) from biomass of the root, litter and necromass were 45,6 %, 32,0 % and 40,0 %, respectively. The average content of soil organic carbon at 0-10 cm depth was 1,16 %, at 10-20 cm depth was 0,78 % and at 20-30 cm depth was 0,64 %,